A influência da exportação no desenvolvimento de arranjos produtivos locais de moda no estado do Rio de Janeiro - Cardoso, Fabio dos Santos (2006)
In recent years, clusters have become a central part in discussions about local and regional economic development, as well as in the elaboration of public policies for generating jobs and income. Concurrent with the discussions about clusters, the subject globalization has also received growing attention from the media in the academic and government fields. Different aspects are considered in the discussions regarding globalization and one of the subjects is the insertion of local economies into international commerce. One of these ways of insertion is by global value chains. This term began to be used at the end of 90s, and refers to the productive value chains dispersed throughout the world, but with integrated production and commercialization. The aim of this thesis is to understand how the exportation process influences the development of fashion clusters, this being done by the insertion of these clusters into the global value chains. Each year, the Brazilian fashion sector seeks to broaden their participation in the global economy by means of insertion into the global value chains. This insertion, however, has caused impacts in specialized clusters of garment manufacturers, such as beach fashion, jeans and women¿s clothing. As a way of identifying these impacts, three cluster manufacturers were studied in the state of Rio de Janeiro, namely Cabo Frio, São Gonçalo and Niterói. The impacts of internationalization on the companies integrated into these three clusters were explored by means of a six-month field study, including semistructured interviews. This internationalization occurs either by direct exportation or by means of inserting these companies into the global value chains. The results of the study points out the opportunities and threats to these companies, as well as shows the importance of more adequate public policies for the development of Brazilian fashion clusters. Among these threats, the possibility of inserting these cluster companies into the global value chains in a captive manner (Gereffi, Humphrey, Sturgeon, 2005) was singled out, placing them ¿under control¿ of the exporting companies. As for opportunities, the participation of government support agencies and improvements in fashion show good alternatives for inserting these companies into the global value chains, making possible autonomous and competitive performance.